2003
DOI: 10.3354/meps249069
|View full text |Cite
|
Sign up to set email alerts
|

Microbial dynamics on diatom aggregates in Øresund, Denmark

Abstract: Size, chemical composition, bacteria, flagellate, and ciliate abundance, bacterial production and growth rates as well as community respiration rates were measured on natural diatom aggregates of different sizes collected by SCUBA divers on 5 subsequent days offshore from northern Zealand, Denmark. Aggregate size was highly variable (0.16 to 524 mm 3 ) throughout the sampling period, whereas aggregate (agg.) dry mass (70 to 390 µg agg. ) and organic carbon content (48 to 130 µg agg.-1 ) varied less. The compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 39 publications
8
74
0
2
Order By: Relevance
“…1). Parameters in these processes are based on empirical data: the growth efficiency of prokaryotes (del Giorgio & Cole 2000), mortality of prokaryotes (Strom 2000, Grossart et al 2003, maximum uptake ratio of hydrolyzed carbon (Smith et al 1992), and the supply rate of organic carbon (on the same order as primary production) (Williams 2000) (see Appendix 2 for details).…”
Section: Methodsmentioning
confidence: 99%
“…1). Parameters in these processes are based on empirical data: the growth efficiency of prokaryotes (del Giorgio & Cole 2000), mortality of prokaryotes (Strom 2000, Grossart et al 2003, maximum uptake ratio of hydrolyzed carbon (Smith et al 1992), and the supply rate of organic carbon (on the same order as primary production) (Williams 2000) (see Appendix 2 for details).…”
Section: Methodsmentioning
confidence: 99%
“…Como constituintes das substâncias húmicas e fúlvicas podem levar a um melhor entendimento dos mecanismos da gênese da matéria orgânica complexa e pela sua susceptibilidade de complexar-se com metais traços, podem controlar a disponibilidade destes no meio aquá-tico (Lombardi & Vieira 2000, Freire-Nordi et al 2005, Gouvêa et al 2005, Nogueira et al 2005. Desde que os polissacarídeos extracelulares podem ser usados como substrato por bactérias (Freire-Nordi & Vieira 1998, Colombo et al 2004, estes componentes podem realizar um importante papel na possível associação específica bactéria/alga (Grossart et al 2003). Também são os principais componentes do carbono orgânico liberado pelas algas e são extremamente variáveis na sua composição monossacarídica e estereo-química.…”
Section: Introductionunclassified
“…Bacteria densely colonize marine snow (Alldredge et al, 1986) and aggregate-associated microbial processes such as enzyme activities have often been found to be elevated relative to the surrounding water (Smith et al, 1992;Ploug et al, 1999;Grossart et al, 2003Grossart et al, , 2007, making marine snow hotspots for carbon remineralization (Azam and Long, 2001). For instance, in the Baltic Sea, Grossart et al (2003) found 100 to 360 times higher cell-specific protease and β-glucosidase activities, respectively, in aggregates compared to water surrounding the aggregates.…”
Section: Introductionmentioning
confidence: 99%